Post-traumatic splenic cyst presenting as epidermoid cyst in spleen: an unusual presentation - Kumar, Vineet; Srivastava, Pallavi (International Journal of Research in Medical Sciences, 2025)
Epidermoid splenic cysts are very rare among primary splenic cysts. The histologic findings show cyst wall lined by stratified squamous epithelium, various theories have emerged regarding the origin of cysts, however controversies still exist. We report a case of young adult male in his 20s presenting with left upper abdominal quadrant pain and distention treated with open surgical procedure. Histopathology and immunohistochemistry findings further confirming the diagnosis as epidermoid splenic cyst. The case is unique in its association with history of trauma and development of true cyst.